Surface Reactions of Low-Energy Argon Ions with Organometallic Precursors - Bilgilisoy, Elif; Thorman, Rachel M.; Yu, Jo Chi; Dunn, Timothy B.; Marbach, Hubertus; Mcelwee-White, Lisa; Fairbrother, D. Howard (Journal of Physical Chemistry C, 2020)
A combination of in situ X-ray photoelectron spectroscopy and mass spectrometry has been used to elucidate the elementary surface reactions initiated by the interaction of low-energy (860 eV) argon ions with three organometallic precursors [Ru(CO)4I2, Co(CO)3NO, and WN(NMe2)3]. The effects of ion exposure on each precursor can be described by a largely sequential series of surface reactions. The initial step involves ion-induced decomposition of the precursor to create a nonvolatile deposit, followed by physical sputtering of the atoms in the deposit. For the precursors that contain CO ligands [Ru(CO)4I2 and Co(CO)3NO], ion-induced decomposition is accompanied by desorption of the majority of the CO groups. This is in marked contrast to previous studies of low-energy electron-induced reactions with the same precursors where precursor decomposition yielded only partial desorption of the CO ligands. Conversely, argon ion bombardment of WN(NMe2)3 led to decomposition without ligand loss. For all three precursors, the initial ion-induced decomposition step was not accompanied by significant desorption of intact precursor molecules, while during subsequent physical sputtering of the deposited atoms, ligand-derived organic and inorganic contaminants were removed at higher rates than the metals. This indicates that controlled ion beam deposition conditions could be used to produce deposits with high metal contents from all three precursors. Comparison of low-energy electron-induced reactions of these three precursors with results of this investigation indicates that secondary electrons do not play an important role in the deposition process, but rather precursor decomposition occurs via efficient ion-molecule energy transfer. These reactions are discussed in the context of focused ion beam-induced deposition.
CRIS-Team Scopus Importer:2020-11-20